Piezo stimulated currents in marble samples: precursory and concurrent-with-failure signals - I. Stavrakas; C. Anastasiadis; D. Triantis; F. Vallianatos (Natural Hazards and Earth System Sciences, 2003)
The Earth’s electric field transient variations are promising candidates of earthquake precursors. In order to study the physical mechanisms of such precursory signals, laboratory experiments of uniaxial compression were carried out. More specifically the behaviour of stressed marble samples from Penteli Mountain was investigated. The samples were subjected to a time-varying uniaxial compression at both variable and constant stress rates. During the first set of experiments weak electric currents were detected during pressure variations. Such Piezo Stimulated Currents (PSC) were detected while stress steps, both positive and negative were applied, the maximum stress never being greater than the elasticity limit. During the second set of experiments stress was applied at a constant rate starting from zero-stress and ending in fracture. In the region beyond the elastic limit a PSC was detected which after reaching a peak suffered a reversal in its polarity just before fracture. In a third set of experiments the same procedure was applied to previously structurally damaged samples taking care not to fracture them. In all cases the PSC followed the variation of stress and moreover it was observed that a linear relationship existed between the PSC maxima and the corresponding stress-rate maxima. The mechanism responsible for the described phenomena can be ascribed to the Moving Charged Dislocations model.